PESANTREN-BASED MANAGEMENT MODEL IN THE MANAGEMENT OF ISLAMIC EDUCATION - Abdul Chalim; Suhari (Adisam Publisher, 2025)
The Pesantren-Based Management Model in Islamic Education Management is an innovative approach that integrates the traditional pesantren education system with modern education management principles. This model combines the strength of Islamic values and traditions that have been rooted in the pesantren system with contemporary learning methods, the latest educational technology, and a curriculum that is relevant to the demands of the times. The goal is to create a holistic, effective, and adaptive Islamic education system that is able to prepare students intellectually, spiritually, and practically to face the challenges of the modern world while maintaining Islamic identity and values. This model emphasises the balance between religious and general education, character development, as well as enhancing soft skills, so as to produce graduates who are not only knowledgeable and noble, but also able to contribute significantly in a global society. The research method used is literature. The results showed that the Pesantren-Based Management Model has significant advantages in integrating traditional Islamic values with modern education management principles. The model successfully combines the strengths of the pesantren system with contemporary educational innovations, creating a holistic approach that emphasises the balance between intellectual, spiritual and practical education. The flexibility and adaptability of this model in the face of changing times, as well as its focus on character building and soft skills development, make it highly relevant to address the needs of Islamic education in the global era. This study concludes that the Pesantren-Based Management Model offers an effective and sustainable solution in the management of Islamic education, with the potential to become a reference for the development of a progressive Islamic education system that remains rooted in fundamental Islamic values.